Opportunistic screening of at risk asymptomatic adolescent children for prediabetes - Krishnappa, Santosh Kumar; Yashoda, H T; Chaitra, K M (Indian Journal of Child Health, 2022)
Background: Type 2 diabetes mellitus (T2DM) once considered an adult disease is now being reported in children and adolescents all over the world due to a parallel increase in obesity. Prediabetes is an intermediate stage between no diabetes and diagnosis of DM. Objective: To screen at risk asymptomatic adolescent children for prediabetes state. Methods: A prospective descriptive study was conducted in the outpatient department of a tertiary care hospital in South India. All adolescent children between the age group of 10 and 18 years with evidence of overweight as per the World Health Organization age and sex specific centile charts for body mass index (BMI) were enrolled. The study period was 18-month. Anthropometric and demographic data were collected among these subjects and investigated for oral glucose tolerance test (OGTT), fasting blood glucose (FBG), and glycosylated hemoglobin (HbA1c) as per the designed protocol. Results: Prediabetes was diagnosed in 13% of the study population with a combination of OGTT, FBG, and HbA1c tests. Prediction of prediabetes by OGTT was 10%, HbA1c 5% and by FBS was 3%. Combination of impaired glucose tolerance test with HbA1c had high sensitivity (92%) and specificity (100%). Conclusions: Our study had 13% population with increasing risk of developing T2DM. Further longitudinal studies are required to screen at risk asymptomatic adolescent children for prediabetes.